The effect of fintech on banking performance in South Africa. - Mugabe, Leo Mandizvidza (Graduate School of Business (GSB), 2023)
This research analysed the potential for a long-run relationship between financial technology (FinTech) firms and the banking sector performance in South Africa (SA) for a period spanning from the year 2000 to 2018. The investigation also sought to examine the effects of FinTech on the banking sector performance and how it differs with the size of the bank. The investigation also determines if there exist causal link(s) between FinTech firm presence and the banking sector performance. Where banking performance is reflected through banking related financial ratios of return on equity (ROE), return on assets (ROA), net interest margin (NIM), and yield on earning assets (YEA). Methodologically, this study used the Autoregressive Distributed Lag (ARDL) model and the Granger Causality test to inform the investigation. ARDL model helped the researcher to establish whether FinTech firm presence has a significant directional relationship with the determinants of performance in the banking sector. The Granger Causality test was used to infer if FinTech drives banking performance. The major results of the ARDL model show that FinTech firm presence was a significant factor in the long-run determinants of ROE, ROA, and YEA at 1% level of significance, whilst only at 10% level for NIM. The results of the Granger Causality test, however, showed that FinTech firm presence cannot be used to predict future RSA banking sector performance. This study concludes that is a relationship between FinTech and the determinants of banking sector performance. However, ROE being the only determinant with a negative relationship. This research also recommends that a closer eye be kept on the thinning of NIM by banks to compete with new FinTech firms as this may lead to risky lending where the cost of debt does not reflect the risk. The banking sector should welcome FinTech as it brings about more efficient banking sector performances. The financial sector benefits from incoming innovation brought about by Fintech firms